Assessment of math abilities before school entry: a tool development - Cruz, Joana; Alves, Diana; Carvalho, Marisa; Mendes, Sofia Abreu; Rodrigues, Bruna; Cadime, Irene (Frontiers in Education, 2024)
The years preceding school entry are pivotal for children to develop fundamental skills that bolster their learning in literacy and math in the following years. Skills like counting and subitizing stand as key predictors of future math abilities. Hence, the availability of universal screening tools is vital to promptly identify children who are lacking in these skills, allowing for tailored classroom practices to meet their needs. This study aimed to develop a mathematical screening tool and assess its psychometric properties. The tool encompasses both group and individual tasks, with the latter evaluating counting, cardinality, subitizing, quantity discrimination, addition, and subtraction. The tool was administered twice to 257 children, aged 5 to 6, in their final year of kindergarten in Portugal, at both the start and end of the school year. The findings reveal that the tasks generally present a low level of difficulty, especially by the end of kindergarten. Factor analysis demonstrated an adequate structure, and all dimensions showed high internal consistency (>.80). There was a medium-to-high intercorrelation among the various tasks. Correlations between task scores at the beginning and end of the school year were high. Furthermore, scores across all tasks correlated with math achievement in the first grade of primary education. These outcomes suggest that the tool is both valid and reliable, making it a useful resource for assessing and intervening in math skills during the critical years before school entry.